Influence of Financial Ratios and Firm Size on Stock Under-pricing in IPO Companies at the Indonesia Stock Exchange (2021–2023) - Camelia Camelia; Mukhzarudfa Mukhzarudfa; Wiralestari Wiralestari (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study delves into the dynamics between selected financial indicators, Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings per Share (EPS), and firm size, and the phenomenon of stock underpricing among firms undertaking Initial Public Offerings (IPOs) on the Indonesia Stock Exchange during 2021–2023. From a population comprising all IPO-listed companies within this period, purposive sampling yielded 124 firms, of which 14 were excluded as statistical outliers, resulting in 110 observations for analysis. Employing a quantitative framework, the research integrates classical assumption diagnostics with multiple linear regression to examine both collective and individual variable effects through F-tests and t-tests, respectively. The findings reveal that ROA and EPS exert significant negative influences on underpricing, aligning with signaling theory, while ROE, DER, and firm size do not demonstrate partial significance. Nonetheless, when considered jointly, all five variables exhibit a statistically significant impact, suggesting that investors may interpret financial signals in aggregate rather than isolation when navigating IPO valuations.